2008
DOI: 10.1108/10610420810864720
|View full text |Cite
|
Sign up to set email alerts
|

The changing price of brand loyalty under perceived time pressure

Abstract: Purpose -This study sets out to investigate the price premium brand-loyal customers would be willing to pay over expectations in order to remain loyal. Design/methodology/approach -A total of 385 consumers were asked price expectations and brand preferences for ten different products. Nonbrand-loyal consumers were asked whether they would buy the cheapest brand or the cheapest brand with a name they recognized. Brand-loyal consumers were asked to imagine they went to buy each product only to discover a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Loyal customers are usually willing to pay more than other customers since they prefer the product or service over others (Jensen and Drozdenko, 2008). In the hospitality context, studies have found that loyal customers express significantly higher brand preferences for airlines and hotels and are willing to pay a premium when facing purchase choices (Mathies and Gudergan, 2012).…”
Section: The Influence Of Customer Loyalty On Customer Willingness Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Loyal customers are usually willing to pay more than other customers since they prefer the product or service over others (Jensen and Drozdenko, 2008). In the hospitality context, studies have found that loyal customers express significantly higher brand preferences for airlines and hotels and are willing to pay a premium when facing purchase choices (Mathies and Gudergan, 2012).…”
Section: The Influence Of Customer Loyalty On Customer Willingness Tomentioning
confidence: 99%
“…Previous studies also report similar relationships between customer loyalty and willingness to pay more. Loyal customers are usually willing to pay more than other customers since they prefer the product or service over others (Jensen and Drozdenko, 2008).…”
Section: The Influence Of Sustainable Hospitality Supply Chain Managementioning
confidence: 99%
“…Customers who are brand loyal are known to be less price-sensitive (Jensen and Drozdenko, 2008;Krishnamurthy and Raj, 1991). By analogy, once a strong relationship develops with the brand, the role that other factors play should start diminishing.…”
Section: H6 (A)mentioning
confidence: 99%
“…Indeed, increasing the overall size of the rebate has been shown to increase the number of consumers who make the rebated purchase (Silk, 2004). Brand loyal consumers who have been shown previously to be less price sensitive (Jensen and Drozdenko, 2008), might view rebate offers as extensions that facilitate brand customer relationships. Purchase expectations and intentions continue to be linked theoretically and empirically with brand loyalty; perhaps more importantly, they are strong predictors of word of mouth communication and purchase recommendations (Ewing, 2000).…”
Section: Discussionmentioning
confidence: 99%